Fibrinolytic and Anticoagulant Therapy in COVID-19 Associated Pulmonary Embolism: A Case Report - Eka Nantha Kusuma, Putu; I Made Prema Putra; I Gusti Ngurah Mahaalit Aribawa (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
Pulmonary thromboembolism is a complication that can occur in coronavirus disease-2019 (COVID-19). Efforts to prevent and therapy for thromboembolism have been a challenge to this date. The side effects of fibrinolytic, anticoagulant, and platelet anti-aggregation therapies, such as hemorrhage, are some of the causes of morbidity and mortality that must be addressed immediately. In this case, the patient received prophylaxis with the anticoagulant enoxaparin and platelet anti-aggregation agents with aspirin and clopidogrel. The COVID-19 patient presented a complication of pulmonary thromboembolism that was established using a computed tomography pulmonary angiography (CTPA) performed on his third day of care (day 14 of onset treatment) due to the patient’s clinical aggravation of pulmonary manifestation. After fibrinolytic therapy had been given, the patient’s clinical condition improved. However, on the 7th day after the provision of recombinant tissue plasminogen activator (r-TPA), the patient experienced a side effect of hemorrhage, and management was undertaken to address these issues by transfusions of blood components, such as cryoprecipitates, thrombocyte concentrate, fresh frozen plasma, and packed red cell. Thromboembolism occurring in COVID-19 patients is based on the Virchow triad concept, comprising endothelial injury, static blood flow, and hypercoagulation. The principle of prevention and management of thromboembolism refers to this concept. Currently, further studies are required to treat thromboembolism and the side effects of fibrinolytic and anticoagulant therapies on COVID-19 patients.